The Challenges of Augmentation Mastopexy in the Massive Weight Loss Patient: Technical Considerations. Issue 5 (May 2017) - Coombs, Demetrius M.; Srivastava, Udayan; Amar, Dalit; Rubin, J. Peter; Gusenoff, Jeffrey A.
Abstract : Background: Augmentation mastopexy in the massive weight loss population is challenging because of poor skin elasticity and lack of inframammary support. Despite several large studies of augmentation mastopexy in the literature, few data exist regarding this unique patient population. The authors examine early postoperative ptosis, implant malposition, and strategies to optimize outcomes. Methods: A retrospective review of massive weight loss patients who underwent augmentation mastopexy from 2003 to 2011 was performed to record age, body mass index, implant characteristics, postoperative ptosis, and implant malposition. Results: Thirty patients were identified with a mean age of 44.8 ± 8.5 years, mean current body mass index of 26.1 ± 3.9 kg/m 2, and mean follow-up time of 283.5 days (range, 7 to 1095 days). Preoperatively, patients mostly presented with grade 3 ptosis (63.3 percent). Five patients (16.7 percent) developed postoperative ptosis within the first 3 months after surgery, with no increase after this time. Implant malposition increased significantly with time: 61.9 percent by 12 months ( p = 0.006), with a median time for implant malposition of 160 days. Postoperative ptosis was significantly related to age ( p = 0.039) and a larger left-side implant ( p = 0.022). Implant malposition was significantly related to higher current body mass index ( p = 0.047), but not to implant size. Two patients (6.6 percent) underwent revision procedures. Conclusion: Massive weight loss patients have an increased risk of early postoperative ptosis or implant malposition, reinforcing the need for appropriate preoperative counseling to manage patient expectations. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : This and Related "Classic" Articles Appear on Prsjournal.Com for Journal Club Discussions.